Cultivating K-12 Student Interest in STEM - Sheldon, Sonora A. (My University, 2019)
In recent years, there has been a tremendous push for teachers to emphasize science, technology, engineering, and mathematics (STEM) education, in all K-12 classes. Teachers play a critical role in student interest and mindset towards STEM fields. This paper examines some of the research related to STEM education in the United States, math anxiety, growth mindset, and the teacher’s role in student interest in STEM. The subsequent study focuses on the teacher role and teaching practices that may encourage or deter students from STEM. It surveys college students between the ages of 17 and 22 about their current STEM interest as well as K-12 experiences with various STEM activities. The study will be conducted through an online survey, and it aims to provide a description of teacher influence on interest in STEM within their students.